Rancang Bangun Sistem Kepegawaian Menggunakan Metode Key Performance Indicator Untuk Rekomendasi Kenaikan Jabatan - Fungky Setiawan; Temi Ardiansah (Journal of Artificial Intelligence and Technology Information (JAITI), 2023)
PT Atosim Lampung Pelayaran is a private company engaged in crossing services, in the process of increasing employee positions it is still carried out directly by employees without any assessment, so that the greater the risk of employees being unable to carry out the work according to the position given so that they are not on target. The system development method uses the Extreme Programming method and the system design uses the UML system design. This study uses system testing using ISO 25010 with aspects of functionality, usability and reliability. The result achieved is a personnel management information system for promotion recommendations using the Key Performance Indicator (KPI) method. The system built can display employee data and decide on employee promotion recommendations, as well as generate reports according to company needs. The results of the tests that have been carried out involving 4 respondents that the conclusion of the quality of the feasibility of the resulting software has a percentage of success with a total average of 93.93%, so it can be concluded that the percentage value obtained indicates